A method for preparing lost foam casting using composite foam plastic microbeads

Through the technical means of composite foam microbeads, combined with the bonding effect of PMMA and PEI with the resin powder, and the crosslinking reaction of crosslinking polymers, the problem of insufficient mold casting in large-scale, thin-wall castings is solved, achieving efficient and environmentally friendly casting effects.

CN119346800BActive Publication Date: 2025-04-01SHENYANG FUSHENG FOAM PLASTIC PROD CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411930001.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-01
Estimated Expiration
2044-12-26

AI Technical Summary

Technical Problem

The existing disappearing mold casting technology is difficult to ensure molding accuracy and quality stability when producing large and thin-walled castings, and there is also the problem of insufficient environmental protection.

Method used

The method of preparing casting disappearance molds is adopted by composite foam microbeads. By combining the dimensional stability of PMMA and PEI with the bonding effect of styrene-methylmethacrylate resin powder, the connection strength between the microbeads is enhanced, and the dimensional accuracy, compressive strength and thermal stability of the disappearance molds are improved through the cross-linking reaction between HDI-PPG-polycaprolactone cross-linked polymer and HDI-trimethylhexyllactone cross-linked polymer.

Benefits of technology

The dimensional accuracy, compressive strength and thermal stability of the vanishing mold are significantly improved, ensuring high-quality production of large and thin-walled castings, and improving environmental protection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

A method for preparing a lost foam casting mold using composite foam plastic microbeads, belonging to the field of casting modeling technology, the present invention utilizes the dimensional stability of PMMA and PEI combined with the bonding effect of styrene-methyl methacrylate resin powder to make the relative position between microbeads more fixed, improve the dimensional accuracy of the lost foam, make the surface of the lost foam smoother and flatter, enhance the compressive strength of the lost foam, better withstand external pressure, and improve the overall thermal stability of the lost foam in a high-temperature casting environment. HDI-PPG-polycaprolactone cross-linked polymer and HDI-trimethylol hexyl lactone cross-linked polymer are designed to be used in combination, limit the movement and deformation of microbeads from different angles, effectively improve the dimensional accuracy of the lost foam, make the surface of the microbeads smoother, enhance the connection strength between microbeads, more efficiently transmit and disperse external pressure, improve the compressive strength of the lost foam, more stably protect the microbeads from thermal deformation, and improve the thermal stability of the lost foam.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of casting modeling, and in particular relates to a method for preparing a casting lost foam with composite foam plastic microbeads. Background Art

[0002] Traditional casting processes, such as sand casting, often require complex mold making and demoulding processes, and the casting accuracy is limited. Driven by the industrial demand for high-precision, complex structure castings and improved production efficiency, lost foam casting technology came into being.

[0003] The origin of lost foam casting can be traced back to the 1950s. Initially, it was mainly used in the production of some small and simple castings. The technology at that time faced many challenges. The performance of the foam-like material was unstable, and a large amount of gas was easily generated during the casting process, resulting in defects such as pores in the castings. In addition, the early process control methods were relatively backward, and it was difficult to accurately grasp key parameters such as pouring speed, temperature and pressure, resulting in uneven casting quality.

[0004] With the development of material science, the research and development of new foam materials has made significant progress. Materials such as polystyrene (EPS) and polymethyl methacrylate (PMMA) have gradually become the mainstream materials for lost foam production. These materials have good formability, low gas emission and certain strength, which can better meet the requirements of casting process. At the same time, the automation level of casting process is constantly improving, and advanced sensor technology and computer control systems are introduced into the lost foam casting process. By real-time monitoring and precise control of various parameters in the pouring process, the generation of casting defects is effectively reduced and the stability of product quality is improved.

[0005] In the industrial field, automobile manufacturing is one of the important application directions of lost foam casting technology. The lost foam casting process is used for automobile engine cylinder blocks, cylinder heads and other parts, which can not only realize the one-time molding of complex internal structures and reduce machining allowances, but also improve production efficiency and reduce production costs. The demand for high-precision and high-performance castings in the aerospace field has also prompted the continuous innovation of lost foam casting technology.

[0006] Although lost foam casting has made great progress, it still faces some problems. For example, for the production of large and thin-walled castings, how to further improve the molding accuracy and quality stability is still the focus of research. In addition, in terms of environmental protection, it is necessary to develop more environmentally friendly foam materials and coatings to reduce harmful gas emissions and waste disposal difficulties during the casting process. Summary of the invention

[0007] The existing lost foam casting still cannot meet the production requirements in terms of molding accuracy and quality stability for the production of large and thin-walled castings, and the environmental protection needs to be continuously improved. The present invention provides a method for preparing a lost foam casting with composite foam plastic microbeads. The present invention combines the dimensional stability of PMMA and PEI with the bonding effect of styrene-methyl methacrylate resin powder to make the relative position between microbeads more fixed, greatly improve the dimensional accuracy of the lost foam, make the surface of the lost foam smoother and flatter, reduce the roughness, significantly enhance the compressive strength of the lost foam, enable it to better withstand external pressure, and improve the overall thermal stability of the lost foam in a high-temperature casting environment. The present invention designs HDI-PPG-polycaprolactone cross-linked polymer and HDI-trimethylol hexyl lactone cross-linked polymer for use, and simultaneously wraps the microbeads, restricts the movement and deformation of the microbeads from different angles, more effectively improves the dimensional accuracy of the lost foam, makes the surface of the microbeads smoother, enhances the connection strength between the microbeads, more efficiently transmits and disperses external pressure, greatly improves the compressive strength of the lost foam, more firmly protects the microbeads from thermal deformation, and significantly improves the thermal stability of the lost foam. The prepared lost foam casting has high quality and is not only suitable for the preparation of ordinary castings, but also particularly suitable for the production of large and thin-walled castings, ensuring the quality of castings and good environmental protection. The specific technical scheme is as follows:

[0008] A method for preparing a lost foam casting mold using composite foam plastic microbeads, the method comprising the following steps:

[0009] S1, raw material preparation:

[0010] Prepare raw materials by mass: 45-55 parts of polystyrene foam microbeads (EPS), 18-22 parts of polymethyl methacrylate foam microbeads (PMMA), 12-16 parts of styrene-methyl methacrylate resin powder, 12-16 parts of polyetherimide foam microbeads (PEI), 6-10 parts of nano-silicon dioxide, 4-8 parts of silicon carbide nanowhiskers, 3-6 parts of HDI-PPG-polycaprolactone cross-linked polymer, 3-6 parts of HDI-trimethylol hexyl lactone cross-linked polymer, 1.5-3.5 parts of calcium stearate, 0.3-1 parts of azodicarbonamide, 0.5-1 parts of dimethyl silicone oil, 0.3-0.8 parts of sodium hexametaphosphate and 0.1-0.3 parts of hindered phenol antioxidant 1010;

[0011] S2, raw material pretreatment:

[0012] S2.1: drying polystyrene foam microbeads (EPS), polymethyl methacrylate foam microbeads (PMMA), styrene-methyl methacrylate resin powder, and polyetherimide foam microbeads (PEI) respectively; drying nano-silicon dioxide and silicon carbide nano-whiskers respectively;

[0013] S2.2: dispersing nano-silicon dioxide in ethanol with a mass of 5 to 10 times the mass of the nano-silicon dioxide to obtain a nano-silicon dioxide dispersion; dispersing silicon carbide nanowhiskers in acetone with a mass of 6 to 10 times the mass of the silicon carbide nanowhiskers to obtain a silicon carbide nanowhiskers dispersion; dissolving sodium hexametaphosphate in deionized water with a mass of 5 to 8 times the mass of the sodium hexametaphosphate to obtain a sodium hexametaphosphate solution;

[0014] S3, premix:

[0015] S3.1: Add the dried polystyrene foam microbeads (EPS), polymethyl methacrylate foam microbeads (PMMA), styrene-methyl methacrylate resin powder, and polyetherimide foam microbeads (PEI) into the mixer in sequence, and stir at a low speed of 300 rpm to 500 rpm for 3 to 5 minutes to mix the microbead system evenly;

[0016] S3.2: Add the nano-silicon dioxide dispersion and the silicon carbide nano-whisker dispersion into the mixer in sequence, and continue stirring at a medium speed of 800 rpm to 1000 rpm for 5 min to 8 min to uniformly disperse the nano-materials in the micro-bead system;

[0017] S3.3: Add the sodium hexametaphosphate solution into the mixer and stir at a high speed of 1200 rpm to 1500 rpm for 3 min to 5 min;

[0018] S4, cross-linking and additive mixing:

[0019] S4.1: Add HDI-PPG-polycaprolactone cross-linked polymer and HDI-trimethylol hexyl lactone cross-linked polymer into the mixer in sequence, stir at a medium speed of 800 rpm to 1000 rpm for 20 min to 30 min at a temperature of 60°C to 80°C, so that the cross-linked polymer is evenly wrapped on the surface of the microbeads and a cross-linking reaction occurs, and evaporate and remove excess ethanol, acetone and deionized water, and cool to room temperature;

[0020] S4.2: Add calcium stearate, azodicarbonamide and dimethyl silicone oil to the mixer in sequence, and stir at a low speed of 300 rpm to 500 rpm for 3 min to 5 min; finally add hindered phenol antioxidant 1010, and continue stirring at a low speed of 300 rpm to 500 rpm for 2 min to 5 min to obtain a mixture;

[0021] S5, Foaming:

[0022] S5.1: Add the mixed material into the mold, set the mold temperature to 60°C to 80°C, press the mold at a pressure of 5MPa to 10MPa for 3min to 5min, and allow the mixed material to foam in the mold to form a preform of the lost foam;

[0023] S5.2: The formed lost foam blank is retained in the mold and subjected to heat preservation treatment at 60°C to 70°C for 12h to 24h to further complete the cross-linking reaction, improve the strength and dimensional stability of the lost foam, and obtain the casting lost foam after cooling and demoulding.

[0024] In S1 of the above method, the particle size range of the polystyrene foam microbeads (EPS), polymethyl methacrylate foam microbeads (PMMA), and polyetherimide foam microbeads (PEI) are all 0.1 mm to 1 mm; the particle size range of the styrene-methyl methacrylate resin powder is all below 0.3 mm.

[0025] In S1 of the above method, the particle size range of the nano-silicon dioxide is below 150 nm; the diameter range of the silicon carbide nano-whisker is 0.2 μm to 0.7 μm, and the length range of the silicon carbide nano-whisker is 10 μm to 35 μm.

[0026] In S2.1 of the above method, the drying temperatures of the polystyrene foam microbeads (EPS), polymethyl methacrylate foam microbeads (PMMA), styrene-methyl methacrylate resin powder, and polyetherimide foam microbeads (PEI) are all 40° C. to 50° C., and the drying times are all 2 h to 3 h.

[0027] In S2.1 of the above method, the drying temperature of the nano-silicon dioxide and the silicon carbide nano-whiskers is 100° C. to 120° C., and the drying time is 1 h to 2 h.

[0028] In S2.2 of the above method, the nano-silicon dioxide is dispersed in ethanol and subjected to ultrasonic treatment at a frequency of 30kHz to 50kHz for 20min to 30min.

[0029] In S2.2 of the above method, the silicon carbide nanowhiskers are dispersed in acetone and ultrasonically treated at a frequency of 40 kHz to 60 kHz for 30 min to 40 min.

[0030] In S5.1 of the above method, the foaming volume ratio of the foam molding is 3 to 5 times.

[0031] The above method further comprises S6, coating application:

[0032] The lost foam casting is coated with lost foam coating by a dipping method, and after drying, a coated lost foam casting is obtained.

[0033] In S6 of the above method, the dipping method comprises the following steps: each dipping time is 3s to 5s, and the dipping is performed 2 to 4 times.

[0034] In S6 of the above method, the coating thickness of the lost foam coating is 0.5 mm to 2 mm.

[0035] In S6 of the above method, the lost foam coating includes the following raw materials in parts by mass: 42 to 48 parts of zircon powder, 12 to 18 parts of silicon carbide titanium MAX phase ceramic material (Ti3SiC2), 22 to 28 parts of phenolic resin, 3.5 to 4.5 parts of sodium carboxymethyl cellulose, 18 to 22 parts of ethanol, 0.6 to 0.8 parts of n-octanol, 0.5 to 1 part of micro powder wax, 1 to 2 parts of sodium hexametaphosphate and 2 to 3 parts of dibutyl phthalate.

[0036] In the above-mentioned lost foam coating, the particle size range of the zircon powder is 5μm to 300μm; the particle size range of the silicon carbide titanium MAX phase ceramic material (Ti3SiC2) is below 3μm; and the particle size range of the micro powder wax is below 30μm.

[0037] The present invention provides a method for preparing a lost foam casting mold using composite foam plastic microbeads, which has the following beneficial effects:

[0038] 1. The lost foam of the present invention contains a specific proportion of polystyrene foam microbeads (EPS), polymethyl methacrylate foam microbeads (PMMA), styrene-methyl methacrylate resin powder, polyetherimide foam microbeads (PEI), nano-silicon dioxide, silicon carbide nano whiskers, HDI-PPG-polycaprolactone cross-linked polymer, HDI-trimethylol hexyl lactone cross-linked polymer, calcium stearate, azodicarbonamide, dimethyl silicone oil, sodium hexametaphosphate and hindered phenol antioxidant 1010. Polystyrene foam microbeads (EPS), polymethyl methacrylate foam microbeads (PMMA) and polyetherimide foam microbeads (PEI) are the main skeleton materials of the lost foam, providing the basic shape and certain strength. The foam microbeads are light and can expand during the foaming process to fill the mold space to form the desired shape. Styrene-methyl methacrylate resin powder plays the role of bonding the microbeads, so that the microbeads are better combined during the cross-linking reaction, foaming and other processes, thereby enhancing the overall strength of the lost foam. After dispersion, nano-silicon dioxide can fill the gaps between micro-beads, play a reinforcing role, and improve the compressive strength of the lost foam. Silicon carbide nano whiskers can further enhance the mechanical properties of the material, and the whisker-like structure can play a role similar to "rebar" inside the material to withstand external forces. HDI-PPG-polycaprolactone cross-linked polymer and HDI-trimethylol hexyl lactone cross-linked polymer undergo cross-linking reactions on the surface of the micro-beads to form a network structure, wrap the micro-beads, and make the micro-beads more closely connected, which helps to improve the dimensional accuracy, roughness, compressive strength and thermal stability of the lost foam; through cross-linking, the deformation of the micro-beads under conditions such as heat can be limited. Calcium stearate acts as a lubricant, facilitating the flow of materials during mixing and molding, and making the distribution of various components more uniform. Azodicarbonamide is a foaming agent that decomposes and produces gas under conditions such as heat to foam the mixture, thereby achieving the required foaming volume ratio. Dimethyl silicone oil can improve the fluidity and demoulding properties of the mixture and prevent the mixture from sticking to the mold. Sodium hexametaphosphate is used to disperse nanomaterials, so that nano-silicon dioxide and silicon carbide nano-whiskers can be better dispersed in the system. Hindered phenol antioxidant 1010 prevents materials from aging and performance degradation due to oxidation during processing and use, and plays an antioxidant role.

[0039] 2. In the preparation method, the microbead drying treatment can remove volatile components such as moisture in the raw materials, improve the homogeneity of subsequent pre-mixing, reduce the difficulty of mixing, and is not prone to adhesion and agglomeration. The nano-silicon dioxide and silicon carbide nano-whiskers are evenly dispersed in the corresponding solvents through ultrasonic treatment to form a dispersion, which is conducive to their uniform distribution in the micro-bead system, play a reinforcing role, and the dispersion helps to improve the quality of the cross-linking reaction. Add a cross-linked polymer and stir at a certain temperature to make the cross-linked polymer undergo a cross-linking reaction on the surface of the micro-beads to form a stable network structure, wrap the micro-beads, enhance the performance of the lost foam, and evaporate and remove excess solvent. After foaming, keep warm at a certain temperature to further complete the cross-linking reaction and improve the strength and dimensional stability of the lost foam. The lost foam coating is applied to the surface of the casting lost foam by a dip coating method, and a coating is formed after drying to improve the fire resistance, wear resistance and thermal stability of the lost foam and protect the lost foam from damage during the casting process.

[0040] 3. The size of PMMA microbeads is relatively stable. During the cross-linking and foaming process, their shape changes are relatively small, which can provide a stable size basis for the lost foam, help maintain the dimensional accuracy of the lost foam, and then better transmit dimensional information during the casting process, so that the dimensional accuracy of the casting is improved. The surface is relatively smooth after foaming. After mixing with other microbeads, the surface roughness of the lost foam can be reduced. After casting, the surface of the casting can be smoother and the appearance quality is better. PMMA has a certain strength and can share external pressure in the microbead system to enhance the compressive resistance of the lost foam. PMMA also has good thermal stability. When heated, its structural changes are relatively small, and it can withstand certain temperature changes during the casting process, thereby improving the thermal stability of the lost foam. The good compressive strength and thermal stability of the lost foam can keep the shape intact during the casting process, prevent defects inside the casting due to the rupture of the lost foam, and thus improve the internal quality of the casting.

[0041] Fourth, styrene-methyl methacrylate resin powder as a binder can make the micro-beads closely bonded, reduce the displacement of micro-beads during processing and use, help maintain the dimensional accuracy of the lost foam, and ensure the shape stability of the lost foam during the casting process, thereby improving the dimensional accuracy of the casting. It can fill the gaps between the micro-beads, make the surface of the lost foam smoother, reduce the roughness, the surface flatness of the lost foam is high, and the appearance of the casting after casting is smoother. By bonding the micro-beads, the strength of each micro-bead is integrated to enhance the overall compressive strength of the lost foam. At high temperatures, its bonding effect can still be maintained, so that the micro-bead system will not loosen due to heat, and the thermal stability is improved. Good bonding effect enables the lost foam to have sufficient strength to resist the scouring of molten metal during the casting process, etc., and reduce the internal defects of the casting caused by damage to the lost foam.

[0042] 5. PEI microbeads have good dimensional stability and can maintain their own shape during the processing, which helps to improve the dimensional accuracy of the lost foam, and thus helps to improve the dimensional accuracy of the casting. Its surface properties can make the surface of the lost foam more delicate and reduce the roughness. Due to the low roughness of the lost foam, the appearance quality of the casting after casting is better. It has high strength and can withstand external pressure, enhancing the compressive capacity of the lost foam. PEI has excellent thermal stability. Under the high temperature environment during the casting process, it can maintain structural stability and improve the thermal stability of the lost foam. The high strength and thermal stability of the lost foam can prevent deformation and cracking during the casting process, thereby improving the internal quality of the casting.

[0043] 6. HDI-PPG-polycaprolactone cross-linked polymer undergoes cross-linking reaction on the surface of micro-beads to form a coating layer, which limits the expansion and movement of micro-beads, thereby improving the dimensional accuracy of the lost foam and the dimensional accuracy of the casting. The surface is smooth, and the cross-linked structure fills part of the gaps between the micro-beads, reducing the surface roughness of the lost foam. The casting has a smoother appearance and better dimensional accuracy after casting. The network structure formed by cross-linking strengthens the connection between the micro-beads, can effectively transmit and disperse external pressure, and improve the compressive strength of the lost foam. The cross-linked polymer can maintain structural stability at high temperatures, prevent the micro-beads from deforming due to heat, and thus improve the thermal stability of the lost foam. During the casting process, good compressive strength and thermal stability enable the lost foam to better resist the impact of molten metal and the influence of high temperature, reduce internal defects of castings, and improve the internal quality of castings.

[0044] 7. HDI-trimethylol hexyl lactone cross-linked polymer wraps the micro-beads through cross-linking reaction, restricts the expansion and displacement of the micro-beads, is conducive to improving the dimensional accuracy of the lost foam, can ensure the shape stability of the lost foam during the casting process, and is conducive to improving the dimensional accuracy of the casting. The surface is smooth, and its cross-linked structure helps to fill the gaps between the micro-beads, reduce the surface roughness of the lost foam, and improve the roughness and dimensional accuracy of the lost foam, so that the appearance of the casting after casting is better. The formed cross-linked network enhances the bonding force between the micro-beads, can better withstand external pressure, and improve the compressive strength of the lost foam. In a high temperature environment, its structure can remain stable, avoid thermal deformation of the micro-beads, and thus improve the thermal stability of the lost foam. During the casting process, its good compressive strength and thermal stability help prevent damage to the lost foam, thereby improving the internal quality of the casting.

[0045] 8. Silicon carbide titanium MAX phase ceramic material (Ti3SiC2) is added to the lost foam coating. Silicon carbide titanium MAX phase ceramic material (Ti3SiC2) can significantly improve the thermal stability of the lost foam. Ti3SiC2 has good thermal conductivity and high temperature stability. During the casting process, when the lost foam is subjected to the thermal shock of the high-temperature molten metal, it can quickly conduct heat to avoid local overheating. At the same time, its own structure is still stable at high temperatures, thereby effectively improving the overall thermal stability of the lost foam.

[0046] Silicon carbide titanium MAX phase ceramic material (Ti3SiC2) has a porous structure. In lost foam casting, when the lost foam is decomposed by heat to produce gas, the Ti3SiC2 pores can absorb part of the gas. The principle is based on physical adsorption, and these pores provide additional space to accommodate the gas. When the gas generated by the decomposition of the lost foam enters the pores, the possibility of gas forming defects such as pores inside the casting can be reduced. Moreover, this porous structure can buffer the pressure changes generated by the gas to a certain extent, making the gas release process smoother. This helps to reduce problems such as surface defects and internal pores in the casting caused by gas escape, thereby improving the quality of the casting.

[0047] In summary, the present invention utilizes the dimensional stability of PMMA and PEI combined with the bonding effect of styrene-methyl methacrylate resin powder to make the relative position between microbeads more fixed, greatly improve the dimensional accuracy of the lost foam, make the surface of the lost foam smoother and flatter, reduce roughness, significantly enhance the compressive strength of the lost foam, enable it to better withstand external pressure, and cooperate with each other in the bonding and retention effect at high temperature, thereby improving the overall thermal stability of the lost foam under the casting high temperature environment. The present invention designs HDI-PPG-polycaprolactone cross-linked polymer and HDI-trimethylol hexyl lactone cross-linked polymer for use, and the two cross-linked polymers simultaneously wrap the microbeads, restrict the movement and deformation of the microbeads from different angles, and more effectively improve the dimensional accuracy of the lost foam. They work together to make the surface of the microbeads smoother, and the cross-linked network better fills the gap between the microbeads, further reducing the roughness of the lost foam. The network structure formed by the two cross-linked polymers is intertwined, which enhances the connection strength between the microbeads, more efficiently transmits and disperses external pressure, and greatly improves the compressive strength of the lost foam. The stable structures of the two cross-linked polymers at high temperatures cooperate with each other, more firmly protect the microbeads from thermal deformation, and significantly improve the thermal stability of the lost foam. The prepared lost foam casting has high quality and is not only suitable for the preparation of ordinary castings, but also particularly suitable for the production of large and thin-walled castings, ensuring the quality of castings and having good environmental protection. DETAILED DESCRIPTION

[0048] The present invention is further described below in conjunction with specific implementation cases, but the present invention is not limited to these embodiments.

[0049] Example 1

[0050] A method for preparing a lost foam casting mold using composite foam plastic microbeads, the method comprising the following steps:

[0051] S1, raw material preparation:

[0052] Prepare raw materials by mass: 50 parts of polystyrene foam microbeads (EPS), 20 parts of polymethyl methacrylate foam microbeads (PMMA), 14 parts of styrene-methyl methacrylate resin powder, 14 parts of polyetherimide foam microbeads (PEI), 8 parts of nano-silicon dioxide, 6 parts of silicon carbide nanowhiskers, 5 parts of HDI-PPG-polycaprolactone cross-linked polymer, 5 parts of HDI-trimethylol hexyl lactone cross-linked polymer, 2 parts of calcium stearate, 0.6 parts of azodicarbonamide, 0.8 parts of dimethyl silicone oil, 0.5 parts of sodium hexametaphosphate and 0.2 parts of hindered phenol antioxidant 1010;

[0053] S2, raw material pretreatment:

[0054] S2.1: Dry polystyrene foam microbeads (EPS), polymethyl methacrylate foam microbeads (PMMA), styrene-methyl methacrylate resin powder, and polyetherimide foam microbeads (PEI) at 45°C for 2.5 hours respectively; dry nano-silicon dioxide and silicon carbide nano-whiskers at 110°C for 1.5 hours respectively;

[0055] S2.2: Disperse nano-silicon dioxide in ethanol with a mass of 8 times that of the nano-silicon dioxide, and perform ultrasonic treatment at a frequency of 40kHz for 25 minutes to obtain a nano-silicon dioxide dispersion; disperse silicon carbide nanowhiskers in acetone with a mass of 8 times that of the silicon carbide nanowhiskers, and perform ultrasonic treatment at a frequency of 50kHz for 35 minutes to obtain a silicon carbide nanowhiskers dispersion; dissolve sodium hexametaphosphate in deionized water with a mass of 6 times that of the sodium hexametaphosphate to obtain a sodium hexametaphosphate solution;

[0056] S3, premix:

[0057] S3.1: Add the dried polystyrene foam microbeads (EPS), polymethyl methacrylate foam microbeads (PMMA), styrene-methyl methacrylate resin powder, and polyetherimide foam microbeads (PEI) into the mixer in sequence, and stir at a low speed of 400 rpm for 4 minutes to mix the microbead system evenly;

[0058] S3.2: Add the nano-silicon dioxide dispersion and the silicon carbide nano-whisker dispersion into the mixer in sequence, and continue stirring at a medium speed of 900 rpm for 6 minutes to evenly disperse the nanomaterials in the microbead system;

[0059] S3.3: Add the sodium hexametaphosphate solution into the mixer and stir at 1300 rpm for 4 min;

[0060] S4, cross-linking and additive mixing:

[0061] S4.1: Add HDI-PPG-polycaprolactone cross-linked polymer and HDI-trimethylol hexyl lactone cross-linked polymer into the mixer in sequence, stir at 900 rpm for 25 min at 70°C to allow the cross-linked polymer to be evenly coated on the surface of the microbeads and undergo a cross-linking reaction, and evaporate and remove excess ethanol, acetone and deionized water to cool to room temperature;

[0062] S4.2: Calcium stearate, azodicarbonamide and dimethyl silicone oil were added to the mixer in sequence, and stirred at a low speed of 400 rpm for 4 min; finally, hindered phenol antioxidant 1010 was added, and stirring was continued at a low speed of 400 rpm for 3 min to obtain a mixture;

[0063] S5, Foaming:

[0064] S5.1: Add the mixed material into the mold, set the mold temperature to 70°C, press the mold at a pressure of 8MPa for 4 minutes, and allow the mixed material to foam in the mold to form a preform of lost foam; the foaming volume ratio is 4 times;

[0065] S5.2: retaining the formed lost foam blank in the mold and heat-insulating it at 65°C for 18 hours to further complete the cross-linking reaction, improve the strength and dimensional stability of the lost foam, and obtain the casting lost foam after cooling and demoulding;

[0066] S6, coating application:

[0067] The lost foam casting was coated with lost foam coating by dipping method, each dipping time was 4s, the dipping was repeated 3 times, and after drying, a coated lost foam casting was obtained, and the coating thickness was 1mm.

[0068] In this embodiment, the lost foam coating includes the following raw materials in parts by mass: 46 parts of zircon powder, 16 parts of silicon carbide titanium MAX phase ceramic material (Ti3SiC2), 25 parts of phenolic resin, 4 parts of sodium carboxymethyl cellulose, 20 parts of ethanol, 0.7 parts of n-octanol, 0.8 parts of micro powder wax, 1.5 parts of sodium hexametaphosphate and 2.5 parts of dibutyl phthalate.

[0069] Example 2

[0070] A method for preparing a lost foam casting mold using composite foam plastic microbeads, the method comprising the following steps:

[0071] S1, raw material preparation:

[0072] Prepare raw materials by mass: 45 parts of polystyrene foam microbeads (EPS), 18 parts of polymethyl methacrylate foam microbeads (PMMA), 12 parts of styrene-methyl methacrylate resin powder, 12 parts of polyetherimide foam microbeads (PEI), 6 parts of nano-silicon dioxide, 4 parts of silicon carbide nanowhiskers, 3 parts of HDI-PPG-polycaprolactone cross-linked polymer, 3 parts of HDI-trimethylol hexyl lactone cross-linked polymer, 1.5 parts of calcium stearate, 0.3 parts of azodicarbonamide, 0.5 parts of dimethyl silicone oil, 0.3 parts of sodium hexametaphosphate and 0.1 parts of hindered phenol antioxidant 1010;

[0073] S2, raw material pretreatment:

[0074] S2.1: Dry polystyrene foam microspheres (EPS), polymethyl methacrylate foam microspheres (PMMA), styrene-methyl methacrylate resin powder, and polyetherimide foam microspheres (PEI) at 40°C for 2 h; dry nano-silicon dioxide and silicon carbide nano-whiskers at 100°C for 1 h;

[0075] S2.2: Disperse nano-silicon dioxide in ethanol with a mass of 5 times that of the nano-silicon dioxide, and perform ultrasonic treatment at a frequency of 30 kHz for 20 minutes to obtain a nano-silicon dioxide dispersion; disperse silicon carbide nanowhiskers in acetone with a mass of 6 times that of the silicon carbide nanowhiskers, and perform ultrasonic treatment at a frequency of 40 kHz for 30 minutes to obtain a silicon carbide nanowhiskers dispersion; dissolve sodium hexametaphosphate in deionized water with a mass of 5 times that of the sodium hexametaphosphate to obtain a sodium hexametaphosphate solution;

[0076] S3, premix:

[0077] S3.1: Add the dried polystyrene foam microbeads (EPS), polymethyl methacrylate foam microbeads (PMMA), styrene-methyl methacrylate resin powder, and polyetherimide foam microbeads (PEI) into the mixer in sequence, and stir at a low speed of 300 rpm for 3 minutes to mix the microbead system evenly;

[0078] S3.2: Add the nano-silicon dioxide dispersion and the silicon carbide nano-whisker dispersion into the mixer in sequence, and continue stirring at a medium speed of 800 rpm for 5 min to evenly disperse the nanomaterials in the microbead system;

[0079] S3.3: Add the sodium hexametaphosphate solution into the mixer and stir at 1200 rpm for 3 min;

[0080] S4, cross-linking and additive mixing:

[0081] S4.1: Add HDI-PPG-polycaprolactone cross-linked polymer and HDI-trimethylol hexyl lactone cross-linked polymer into the mixer in sequence, stir at 800 rpm for 20 min at 60°C to allow the cross-linked polymer to be evenly coated on the surface of the microbeads and undergo a cross-linking reaction, and evaporate and remove excess ethanol, acetone and deionized water to cool to room temperature;

[0082] S4.2: Calcium stearate, azodicarbonamide and dimethyl silicone oil were added to the mixer in sequence, and stirred at a low speed of 300 rpm for 3 min; finally, hindered phenol antioxidant 1010 was added, and the mixture was stirred at a low speed of 300 rpm for 2 min to obtain a mixture;

[0083] S5, Foaming:

[0084] S5.1: Add the mixed material into the mold, set the mold temperature to 60°C, press the mold at a pressure of 5MPa for 3 minutes, and allow the mixed material to foam in the mold to form a preform of lost foam; the foaming volume ratio is 3 times;

[0085] S5.2: retaining the formed lost foam blank in the mold and heat-insulating it at 60° C. for 12 hours to further complete the cross-linking reaction, improve the strength and dimensional stability of the lost foam, and obtain the casting lost foam after cooling and demoulding;

[0086] S6, coating application:

[0087] The lost foam casting was coated with lost foam coating by dipping method, each dipping time was 3s, the dipping was repeated twice, and after drying, a coated lost foam casting was obtained, and the coating thickness was 0.5 mm.

[0088] In this embodiment, the lost foam coating includes the following raw materials in parts by mass: 42 parts of zircon powder, 12 parts of silicon carbide titanium MAX phase ceramic material (Ti3SiC2), 22 parts of phenolic resin, 3.5 parts of sodium carboxymethyl cellulose, 18 parts of ethanol, 0.6 parts of n-octanol, 0.5 parts of micro powder wax, 1 part of sodium hexametaphosphate and 2 parts of dibutyl phthalate.

[0089] Example 3

[0090] A method for preparing a lost foam casting mold using composite foam plastic microbeads, the method comprising the following steps:

[0091] S1, raw material preparation:

[0092] Prepare raw materials by mass: 45 parts of polystyrene foam microbeads (EPS), 22 parts of polymethyl methacrylate foam microbeads (PMMA), 12 parts of styrene-methyl methacrylate resin powder, 16 parts of polyetherimide foam microbeads (PEI), 6 parts of nano-silicon dioxide, 8 parts of silicon carbide nanowhiskers, 3 parts of HDI-PPG-polycaprolactone cross-linked polymer, 6 parts of HDI-trimethylol hexyl lactone cross-linked polymer, 1.5 parts of calcium stearate, 1 part of azodicarbonamide, 0.5 parts of dimethyl silicone oil, 0.8 parts of sodium hexametaphosphate and 0.1 parts of hindered phenol antioxidant 1010;

[0093] S2, raw material pretreatment:

[0094] S2.1: Dry polystyrene foam microspheres (EPS), polymethyl methacrylate foam microspheres (PMMA), styrene-methyl methacrylate resin powder, and polyetherimide foam microspheres (PEI) at 50°C for 2 h; dry nano-silicon dioxide and silicon carbide nano-whiskers at 120°C for 1 h;

[0095] S2.2: Disperse nano-silicon dioxide in ethanol with a mass of 10 times that of the nano-silicon dioxide, and perform ultrasonic treatment at a frequency of 30 kHz for 30 minutes to obtain a nano-silicon dioxide dispersion; disperse silicon carbide nanowhiskers in acetone with a mass of 6 times that of the silicon carbide nanowhiskers, and perform ultrasonic treatment at a frequency of 60 kHz for 30 minutes to obtain a silicon carbide nanowhiskers dispersion; dissolve sodium hexametaphosphate in deionized water with a mass of 8 times that of the sodium hexametaphosphate to obtain a sodium hexametaphosphate solution;

[0096] S3, premix:

[0097] S3.1: Add the dried polystyrene foam microbeads (EPS), polymethyl methacrylate foam microbeads (PMMA), styrene-methyl methacrylate resin powder, and polyetherimide foam microbeads (PEI) into the mixer in sequence, and stir at a low speed of 300 rpm for 5 minutes to mix the microbead system evenly;

[0098] S3.2: Add the nano-silicon dioxide dispersion and the silicon carbide nano-whisker dispersion into the mixer in sequence, and continue stirring at a medium speed of 800 rpm for 8 minutes to evenly disperse the nanomaterials in the microbead system;

[0099] S3.3: Add the sodium hexametaphosphate solution into the mixer and stir at 1200 rpm for 5 min;

[0100] S4, cross-linking and additive mixing:

[0101] S4.1: Add HDI-PPG-polycaprolactone cross-linked polymer and HDI-trimethylol hexyl lactone cross-linked polymer into the mixer in sequence, stir at 1000 rpm for 20 min at 60°C to allow the cross-linked polymer to be evenly coated on the surface of the microbeads and undergo a cross-linking reaction, and evaporate and remove excess ethanol, acetone and deionized water to cool to room temperature;

[0102] S4.2: Calcium stearate, azodicarbonamide and dimethyl silicone oil were added to the mixer in sequence, and stirred at a low speed of 500 rpm for 3 min; finally, hindered phenol antioxidant 1010 was added, and the mixture was stirred at a low speed of 500 rpm for 2 min to obtain a mixture;

[0103] S5, Foaming:

[0104] S5.1: Add the mixed material into the mold, set the mold temperature to 80°C, press the mold at a pressure of 5MPa for 5min, and allow the mixed material to foam in the mold to form a preform of lost foam; the foaming volume ratio is 3 times;

[0105] S5.2: retaining the formed lost foam blank in the mold and heat-insulating it at 70° C. for 12 hours to further complete the cross-linking reaction, improve the strength and dimensional stability of the lost foam, and obtain the casting lost foam after cooling and demoulding;

[0106] S6, coating application:

[0107] The lost foam casting was coated with lost foam coating by dipping method, each dipping time was 5s, the dipping was repeated 3 times, and after drying, a coated lost foam casting was obtained, and the coating thickness was 1.2 mm.

[0108] In this embodiment, the lost foam coating includes the following raw materials in parts by mass: 42 parts of zircon powder, 18 parts of silicon carbide titanium MAX phase ceramic material (Ti3SiC2), 22 parts of phenolic resin, 4.5 parts of sodium carboxymethyl cellulose, 19 parts of ethanol, 0.8 parts of n-octanol, 0.5 parts of micro powder wax, 2 parts of sodium hexametaphosphate and 2 parts of dibutyl phthalate.

[0109] Example 4

[0110] A method for preparing a lost foam casting mold using composite foam plastic microbeads, the method comprising the following steps:

[0111] S1, raw material preparation:

[0112] Prepare raw materials by mass: 55 parts of polystyrene foam microbeads (EPS), 22 parts of polymethyl methacrylate foam microbeads (PMMA), 16 parts of styrene-methyl methacrylate resin powder, 16 parts of polyetherimide foam microbeads (PEI), 10 parts of nano-silicon dioxide, 8 parts of silicon carbide nanowhiskers, 6 parts of HDI-PPG-polycaprolactone cross-linked polymer, 6 parts of HDI-trimethylol hexyl lactone cross-linked polymer, 3.5 parts of calcium stearate, 1 part of azodicarbonamide, 1 part of dimethyl silicone oil, 0.8 parts of sodium hexametaphosphate and 0.3 parts of hindered phenol antioxidant 1010;

[0113] S2, raw material pretreatment:

[0114] S2.1: Dry polystyrene foam microspheres (EPS), polymethyl methacrylate foam microspheres (PMMA), styrene-methyl methacrylate resin powder, and polyetherimide foam microspheres (PEI) at 50°C for 3 h; dry nano-silicon dioxide and silicon carbide nano-whiskers at 120°C for 2 h;

[0115] S2.2: Disperse nano-silicon dioxide in ethanol with a mass of 10 times that of the nano-silicon dioxide, and perform ultrasonic treatment at a frequency of 50 kHz for 30 minutes to obtain a nano-silicon dioxide dispersion; disperse silicon carbide nanowhiskers in acetone with a mass of 10 times that of the silicon carbide nanowhiskers, and perform ultrasonic treatment at a frequency of 60 kHz for 40 minutes to obtain a silicon carbide nanowhiskers dispersion; dissolve sodium hexametaphosphate in deionized water with a mass of 8 times that of the sodium hexametaphosphate to obtain a sodium hexametaphosphate solution;

[0116] S3, premix:

[0117] S3.1: Add the dried polystyrene foam microbeads (EPS), polymethyl methacrylate foam microbeads (PMMA), styrene-methyl methacrylate resin powder, and polyetherimide foam microbeads (PEI) into the mixer in sequence, and stir at a low speed of 500 rpm for 5 minutes to mix the microbead system evenly;

[0118] S3.2: Add the nano-silicon dioxide dispersion and the silicon carbide nano-whisker dispersion into the mixer in sequence, and continue stirring at a medium speed of 1000 rpm for 8 minutes to evenly disperse the nanomaterials in the microbead system;

[0119] S3.3: Add the sodium hexametaphosphate solution into the mixer and stir at 1500 rpm for 5 min;

[0120] S4, cross-linking and additive mixing:

[0121] S4.1: Add HDI-PPG-polycaprolactone cross-linked polymer and HDI-trimethylol hexyl lactone cross-linked polymer into the mixer in sequence, stir at 1000 rpm for 30 min at 80°C to allow the cross-linked polymer to be evenly coated on the surface of the microbeads and undergo a cross-linking reaction, and evaporate and remove excess ethanol, acetone and deionized water to cool to room temperature;

[0122] S4.2: Calcium stearate, azodicarbonamide and dimethyl silicone oil were added to the mixer in sequence, and stirred at a low speed of 500 rpm for 5 min; finally, hindered phenol antioxidant 1010 was added, and the mixture was stirred at a low speed of 500 rpm for 5 min to obtain a mixture;

[0123] S5, Foaming:

[0124] S5.1: Add the mixed material into the mold, set the mold temperature to 80°C, press the mold at a pressure of 10MPa for 5 minutes, and allow the mixed material to foam in the mold to form a preform of lost foam; the foaming volume ratio is 5 times;

[0125] S5.2: retaining the formed lost foam blank in the mold and heat-treating it at 70°C for 24 hours to further complete the cross-linking reaction, improve the strength and dimensional stability of the lost foam, and obtain the casting lost foam after cooling and demoulding;

[0126] S6, coating application:

[0127] The lost foam casting was coated with lost foam coating by dipping method, each dipping time was 5s, and the dipping was repeated 4 times. After drying, the coated lost foam casting was obtained, and the coating thickness was 2mm.

[0128] In this embodiment, the lost foam coating includes the following raw materials in parts by mass: 48 parts of zircon powder, 18 parts of silicon carbide titanium MAX phase ceramic material (Ti3SiC2), 28 parts of phenolic resin, 4.5 parts of sodium carboxymethyl cellulose, 22 parts of ethanol, 0.8 parts of n-octanol, 1 part of micro powder wax, 2 parts of sodium hexametaphosphate and 3 parts of dibutyl phthalate.

[0129] Example 5

[0130] A method for preparing a lost foam casting mold using composite foam plastic microbeads, the method comprising the following steps:

[0131] S1, raw material preparation:

[0132] Prepare raw materials by mass: 55 parts of polystyrene foam microbeads (EPS), 18 parts of polymethyl methacrylate foam microbeads (PMMA), 16 parts of styrene-methyl methacrylate resin powder, 12 parts of polyetherimide foam microbeads (PEI), 10 parts of nano-silicon dioxide, 4 parts of silicon carbide nanowhiskers, 6 parts of HDI-PPG-polycaprolactone cross-linked polymer, 3 parts of HDI-trimethylol hexyl lactone cross-linked polymer, 3.5 parts of calcium stearate, 0.3 parts of azodicarbonamide, 1 part of dimethyl silicone oil, 0.3 parts of sodium hexametaphosphate and 0.3 parts of hindered phenol antioxidant 1010;

[0133] S2, raw material pretreatment:

[0134] S2.1: Dry polystyrene foam microspheres (EPS), polymethyl methacrylate foam microspheres (PMMA), styrene-methyl methacrylate resin powder, and polyetherimide foam microspheres (PEI) at 40°C for 3 h; dry nano-silicon dioxide and silicon carbide nano-whiskers at 100°C for 2 h;

[0135] S2.2: Disperse nano-silicon dioxide in ethanol with a mass of 5 times that of the nano-silicon dioxide, and perform ultrasonic treatment at a frequency of 50kHz for 20 minutes to obtain a nano-silicon dioxide dispersion; disperse silicon carbide nanowhiskers in acetone with a mass of 10 times that of the silicon carbide nanowhiskers, and perform ultrasonic treatment at a frequency of 40kHz for 40 minutes to obtain a silicon carbide nanowhiskers dispersion; dissolve sodium hexametaphosphate in deionized water with a mass of 5 times that of the sodium hexametaphosphate to obtain a sodium hexametaphosphate solution;

[0136] S3, premix:

[0137] S3.1: Add the dried polystyrene foam microbeads (EPS), polymethyl methacrylate foam microbeads (PMMA), styrene-methyl methacrylate resin powder, and polyetherimide foam microbeads (PEI) into the mixer in sequence, and stir at a low speed of 500 rpm for 3 minutes to mix the microbead system evenly;

[0138] S3.2: Add the nano-silicon dioxide dispersion and the silicon carbide nano-whisker dispersion into the mixer in sequence, and continue stirring at a medium speed of 1000 rpm for 5 minutes to evenly disperse the nanomaterials in the microbead system;

[0139] S3.3: Add the sodium hexametaphosphate solution into the mixer and stir at 1500 rpm for 3 min;

[0140] S4, cross-linking and additive mixing:

[0141] S4.1: Add HDI-PPG-polycaprolactone cross-linked polymer and HDI-trimethylol hexyl lactone cross-linked polymer into the mixer in sequence, stir at 800 rpm for 30 min at 80°C to allow the cross-linked polymer to be evenly coated on the surface of the microbeads and undergo a cross-linking reaction, and evaporate and remove excess ethanol, acetone and deionized water to cool to room temperature;

[0142] S4.2: Calcium stearate, azodicarbonamide and dimethyl silicone oil were added to the mixer in sequence, and stirred at a low speed of 300 rpm for 5 min; finally, hindered phenol antioxidant 1010 was added, and the mixture was stirred at a low speed of 300 rpm for 5 min to obtain a mixture;

[0143] S5, Foaming:

[0144] S5.1: Add the mixed material into the mold, set the mold temperature to 60°C, press the mold at a pressure of 8MPa for 3 minutes, and allow the mixed material to foam in the mold to form a lost foam blank; the foaming volume ratio is 3.5 times;

[0145] S5.2: retaining the formed lost foam blank in the mold and heat-treating it at 65°C for 20 hours to further complete the cross-linking reaction, improve the strength and dimensional stability of the lost foam, and obtain the casting lost foam after cooling and demoulding;

[0146] S6, coating application:

[0147] The lost foam casting was coated with lost foam coating by dipping method, each dipping time was 4s, the dipping was repeated twice, and after drying, a coated lost foam casting was obtained, and the coating thickness was 0.8mm.

[0148] In this embodiment, the lost foam coating includes the following raw materials in parts by mass: 48 parts of zircon powder, 12 parts of silicon carbide titanium MAX phase ceramic material (Ti3SiC2), 28 parts of phenolic resin, 3.5 parts of sodium carboxymethyl cellulose, 21 parts of ethanol, 0.6 parts of n-octanol, 1 part of micro powder wax, 1 part of sodium hexametaphosphate and 3 parts of dibutyl phthalate.

[0149] Example 6

[0150] The lost foam casting of Example 1 was used; the lost foam casting was not coated with lost foam coating.

[0151] The sources of raw materials used in the above embodiments are as follows: polystyrene foam beads (EPS) are from Shanghai Weixin Trading Co., Ltd., model ES, density 0.02g / cm³; polymethyl methacrylate foam beads (PMMA) are from Dongguan Huayun Plastic Raw Materials Co., Ltd., model CM-211, density 1.18g / cm³; styrene-methyl methacrylate resin powder is from Chimei Industrial, model PM-600, density 1.05g / cm³; polyetherimide foam beads (PEI) are from Dongguan Zhonghuan Plastic Co., Ltd., Model 1000-1000, density 1.27g / cm³; HDI-PPG-polycaprolactone cross-linked polymer comes from Shanghai Yuyu New Material Technology Co., Ltd., model sbs4204; HDI-trimethylol hexyl lactone cross-linked polymer comes from Wuhan Huaxiang Kejie Biotechnology Co., Ltd., model hxkj2024; azodicarbonamide comes from Shanghai Kimi Biotechnology Co., Ltd.; dimethyl silicone oil comes from Shandong Shuntai New Materials Co., Ltd., model GB201-50; phenolic resin comes from Jining Tangyi Chemical Co., Ltd., model 2123. Sodium carboxymethyl cellulose comes from Hebei Chaoyan New Material Technology Co., Ltd.

[0152] The particle size indicators of the raw materials used in the above embodiments are as follows: the particle size ranges of polystyrene foam microbeads (EPS), polymethyl methacrylate foam microbeads (PMMA), and polyetherimide foam microbeads (PEI) are all 0.1mm to 1mm; the particle size range of styrene-methyl methacrylate resin powder is all below 0.3mm; the particle size range of nano-silicon dioxide is below 150nm; the diameter range of silicon carbide nanowhiskers is 0.2μm to 0.7μm, and the length range of silicon carbide nanowhiskers is 10μm to 35μm; the particle size range of zircon powder is 5μm to 300μm; the particle size range of silicon carbide titanium MAX phase ceramic material (Ti3SiC2) is below 3μm; the particle size range of micropowder wax is below 30μm.

[0153] Comparative Example 1

[0154] The raw material does not contain polymethyl methacrylate foam plastic microbeads (PMMA), and the mass fraction of polymethyl methacrylate foam plastic microbeads (PMMA) is replaced by polystyrene foam plastic microbeads (EPS); other parameters and methods are the same as in Example 1.

[0155] Comparative Example 2

[0156] The raw material does not contain styrene-methyl methacrylate resin powder, and the mass fraction of styrene-methyl methacrylate resin powder is replaced by polystyrene foam plastic microbeads (EPS); other parameters and methods are the same as in Example 1.

[0157] Comparative Example 3

[0158] The raw material does not contain polyetherimide foam microbeads (PEI), and the mass fraction of polyetherimide foam microbeads (PEI) is replaced by polystyrene foam plastic microbeads (EPS); other parameters and methods are the same as in Example 1.

[0159] Comparative Example 4

[0160] The raw materials do not contain polymethyl methacrylate foam plastic microbeads (PMMA), styrene-methyl methacrylate resin powder, and polyetherimide foam microbeads (PEI), and the mass fractions of each component are replaced by polystyrene foam plastic microbeads (EPS); other parameters and methods are the same as in Example 1.

[0161] Comparative Example 5

[0162] The raw material does not contain HDI-PPG-polycaprolactone crosslinked polymer; other parameters and methods are the same as in Example 1.

[0163] Comparative Example 6

[0164] The raw material does not contain HDI-trimethylol hexyl lactone crosslinked polymer; other parameters and methods are the same as in Example 1.

[0165] Comparative Example 7

[0166] The raw material does not contain HDI-PPG-polycaprolactone crosslinked polymer and HDI-trimethylol hexyl lactone crosslinked polymer; other parameters and methods are the same as in Example 1.

[0167] Comparative Example 8

[0168] In the preparation method, nano-silicon dioxide dispersion and silicon carbide nano-whisker dispersion are not prepared in S2.2; nano-silicon dioxide and silicon carbide nano-whisker are directly added in S3.2; other parameters and methods are the same as in Example 1.

[0169] Comparative Example 9

[0170] No silicon carbide titanium MAX phase ceramic material (Ti3SiC2) is added to the lost foam coating, and the mass fraction of silicon carbide titanium MAX phase ceramic material (Ti3SiC2) is replaced by zircon powder; other parameters and methods are the same as in Example 1.

[0171] Comparative Example 10

[0172] In the lost foam coating, the mass fraction of titanium silicon carbide MAX phase ceramic material (Ti3SiC2) is 8 parts, and the mass fraction of zircon powder is 54 parts; other parameters and methods are the same as in Example 1.

[0173] The lost foam castings prepared in the above-mentioned embodiments and comparative examples were tested.

[0174] 1. Design dimensions of lost foam casting samples

[0175] For large and thin-walled castings, the sample (before coating) is a rectangular lost foam with the design dimensions of 500mm long, 300mm wide, 200mm high and 5mm thick. Such dimensions can reflect the characteristics of large and thin walls and facilitate subsequent inspection operations and result analysis.

[0176] 2. Testing items for lost foam casting

[0177] (1) Dimensional accuracy inspection (before painting):

[0178] Use a high-precision three-coordinate measuring machine to place the lost foam on the measuring platform and fix it. First, measure the overall dimensions in the three directions of length, width and height. Select at least 5 measuring points evenly in each direction, record the measurement data and calculate the average value. For the wall thickness, select 3 different positions along the length and width directions on different sides of the model (top, bottom, side) for measurement. Each position measures the wall thickness of 4 points up, down, left and right, totaling 12 measurement points on each side, and calculate the average value and standard deviation. Qualified standard judgment: The dimensional tolerance of length, width and height is set to ±1mm, that is, the measured average value should be within the range of 499mm~501mm (length), 299mm~301mm (width), and 199mm~201mm (height); the tolerance of wall thickness is set to ±0.3mm, the average wall thickness should be between 4.7mm~5.3mm, and the standard deviation should be less than 0.1mm to ensure the uniformity of wall thickness. All measurement data are judged to be qualified within the specified range, and 50 samples are prepared respectively, and the qualified rate is calculated. The results are shown in Table 1 below.

[0179] (2) Roughness measurement (before painting):

[0180] Using a roughness meter, 5 measurement areas were evenly selected on different surfaces (top, bottom, and side) of the lost foam. Each area was measured 3 times, and the average value was taken as the roughness value Ra of the area. Finally, the average roughness value of all areas was calculated. Three parallel samples were made for each type, and the average test results are shown in Table 1 below.

[0181] (3) Compressive strength test:

[0182] Place the lost foam on the center of the platform of the universal material testing machine and adjust the position so that the pressure can be evenly applied to the model. Set the loading rate to 1mm / min, start the testing machine to apply pressure, and record the pressure-displacement curve. Continue loading until the lost foam is obviously damaged, and record the maximum pressure value F at the time of damage. Calculate the compressive strength σ according to the formula σ=F / A (where A is the force-bearing area, for the top area of ​​the cuboid A=length×width). Make 3 parallel samples for each type, and the average test results are shown in Table 1 below.

[0183] (4) Thermal stability test:

[0184] Place the lost foam sample in a thermogravimetric analyzer, set the heating rate to 10℃ / min, and heat from room temperature to 500℃, and keep it for 3min. Record the mass of the sample every 50℃, draw a mass-temperature curve, and calculate the mass loss rate at 500℃. Measure the key dimensions (length, width, height, wall thickness) of the lost foam before and after heating at 500℃, and calculate the dimensional change rate. Make 3 flat samples of each type, and the average test results are shown in Table 1 below.

[0185] (5) Environmental testing (for coatings):

[0186] Volatile organic compound (VOC) content detection: gas chromatography is used for detection. Take 1g of lost foam coating sample, place it in a sealed sample bottle, and volatilize the VOC in the coating at 40℃ for 1 hour. Then use gas chromatograph to analyze the composition and content of the volatile gas. The results show that the VOC content of each lost foam coating is less than 150g / L.

[0187] Table 1 Testing results of lost foam casting

[0188]

[0189] From the above results, it can be seen that the casting lost molds of Examples 1 to 6 have very good performance, low surface roughness, high compressive strength, good thermal stability, and good environmental protection. From the results of Comparative Examples 1 to 4, it can be seen that the performance of the lost mold is reduced and unstable when polymethyl methacrylate foam plastic microbeads (PMMA), styrene-methyl methacrylate resin powder or polyetherimide foam microbeads (PEI) are missing; at the same time, polymethyl methacrylate foam plastic microbeads (PMMA), styrene-methyl methacrylate resin powder and polyetherimide foam microbeads (PEI) are not added, and the performance of the lost mold is greatly reduced. From the results of Comparative Examples 5 to 7, it can be seen that the performance of the lost mold is reduced and unstable when HDI-PPG-polycaprolactone cross-linked polymer or HDI-trimethylol hexyl lactone cross-linked polymer is missing; at the same time, HDI-PPG-polycaprolactone cross-linked polymer and HDI-trimethylol hexyl lactone cross-linked polymer are not added, which seriously affects the cross-linking reaction of each component and greatly reduces the performance of the lost mold. From the results of Comparative Example 8, it can be seen that if the nano-silicon dioxide dispersion and the silicon carbide nano-whisker dispersion are not prepared, the components are mixed and dispersed unevenly during mixing, resulting in a low precision qualified rate of the lost foam and reduced other properties. From the results of Comparative Examples 9 and 10, it can be seen that if no or a small amount of silicon carbide titanium MAX phase ceramic material (Ti3SiC2) is added to the lost foam coating, the thermal stability of the lost foam is reduced. The silicon carbide titanium MAX phase ceramic material (Ti3SiC2) can effectively improve the protectiveness of the coating, thereby improving the thermal stability of the lost foam.

[0190] 3. Inspection items of casting quality after casting

[0191] In order to comprehensively evaluate the applicability of lost foam, aluminum alloy is selected as the casting metal liquid. Aluminum alloy has good casting performance, strength and corrosion resistance, is suitable for the production of various types of castings, and has good compatibility with lost foam casting process, which can effectively test the effect of lost foam in non-ferrous metal casting. Its composition (mass percentage) is designed as follows: aluminum (Al) 90%, silicon (Si) 6%, magnesium (Mg) 0.6%, copper (Cu) 2.5%, and the balance is other trace elements (the sum of iron, manganese, zinc and other elements); casting temperature 740℃.

[0192] 1. Casting appearance inspection:

[0193] The casting was placed on a well-lit inspection table with a white background, and the casting surface was visually inspected from different angles (360° rotation horizontally and from top to bottom vertically). The inspection content included whether there were defects such as insufficient pouring, cold shut, pores, shrinkage cavities, slag inclusions, sand holes, cracks, etc. The inspection results are shown in Table 2 below.

[0194] Casting appearance inspection evaluation grade standard:

[0195] Level 1 (excellent): There are no visible defects on the casting surface, the surface is smooth and the color is uniform. There are no under-casting, cold shut, pores, shrinkage holes, slag inclusions, sand holes and cracks.

[0196] Level 2 (good): There are a few minor defects. The diameter of the pores is less than 1mm, and the number does not exceed 5 / 100cm²; very slight cold shut marks are allowed, but they do not affect the overall appearance and performance of the casting; slight slag inclusions, the total area of ​​which is less than 0.1% of the surface area of ​​the casting; no shrinkage cavities, sand holes and cracks.

[0197] Level 3 (qualified): There are some obvious defects, but they are still within the acceptable range. The diameter of the pores is 1mm to 3mm, and the number is 6 / 100cm² to 10 / 100cm²; the cold shut phenomenon is obvious, but it does not penetrate the main parts of the casting; the total area of ​​slag inclusions is 0.1% to 0.3% of the surface area of ​​the casting; there are a small number of tiny shrinkage cavities (less than 3mm in diameter), and the number of sand holes does not exceed 3 / 100cm²; there are no cracks.

[0198] Level 4 (unqualified): There are defects that seriously affect the performance and appearance of the casting. The diameter of the pores is greater than 3mm, and the number exceeds 10 / 100cm²; there is a penetrating cold shut; the total area of ​​slag inclusions exceeds 0.3% of the surface area of ​​the casting; there are large shrinkage cavities (diameter greater than 3mm) or more sand holes (the number exceeds 3 / 100cm²); there are cracks.

[0199] 2. Casting dimensional accuracy detection:

[0200] The key dimensions (length, width, height, and wall thickness) of the castings were measured using a three-coordinate measuring machine. Each dimension was measured at least in five different locations. The average value was taken and compared with the design dimension, and the dimensional deviation was calculated. The test results are shown in Table 2 below.

[0201] 3. Internal quality inspection of castings (X-ray flaw detection):

[0202] The casting was placed on the inspection table of the X-ray flaw detection equipment and irradiated with X-rays to analyze whether there were defects such as shrinkage, pores, and inclusions inside. The test results are shown in Table 2 below.

[0203] Casting internal quality evaluation grade standard:

[0204] Level 1 (excellent): Almost no internal defects. The diameter of the pores is less than 0.3mm, and the number does not exceed 3 / 100cm³; the proportion of shrinkage area to the volume of the casting is less than 1%; there are no inclusions.

[0205] Level 2 (good): There are a few tiny internal defects. The diameter of the pores is 0.3mm to 0.6mm, and the number is 4 / 100cm³ to 8 / 100cm³; the proportion of shrinkage area to the volume of the casting is 1% to 3%; there are a few tiny inclusions (the longest dimension is less than 1mm), and the number does not exceed 3 / 100cm³.

[0206] Level 3 (qualified): The internal defects are obvious, but it can still be used. The diameter of the pores is 0.6mm~1mm, and the number is 9 / 100cm³~15 / 100cm³; the proportion of shrinkage area to the volume of the casting is 3%~6%; the number of inclusions (the longest dimension is 1mm~3mm) is 4 / 100cm³~8 / 100cm³.

[0207] Level 4 (unqualified): serious internal defects, not meeting the use requirements. The diameter of the pores is greater than 1mm, and the number exceeds 15 / 100cm³; the proportion of shrinkage area to the volume of the casting exceeds 6%; the number of inclusions (the longest dimension is greater than 3mm) exceeds 8 / 100cm³ or there are large inclusions (the longest dimension is greater than 10mm).

[0208] Table 2 Test results of casting quality

[0209]

[0210] From the above results, it can be seen that the castings prepared by casting lost foam in Examples 1 to 6 have good appearance and internal quality, no visible defects on the casting surface, almost no defects inside, and high dimensional accuracy; the quality of large-size, thin-walled castings can be guaranteed. From the results of Comparative Examples 1 to 4, it can be seen that the quality of the castings is reduced when the lost foam lacks polymethyl methacrylate foam plastic microbeads (PMMA), styrene-methyl methacrylate resin powder or polyetherimide foam microbeads (PEI); the quality of the castings is greatly reduced when the lost foam does not add polymethyl methacrylate foam plastic microbeads (PMMA), styrene-methyl methacrylate resin powder and polyetherimide foam microbeads (PEI). From the results of Comparative Examples 5 to 7, it can be seen that the quality of the castings is reduced when the lost foam lacks HDI-PPG-polycaprolactone cross-linked polymer or HDI-trimethylol hexyl lactone cross-linked polymer; the quality of the castings is greatly reduced when the lost foam does not add HDI-PPG-polycaprolactone cross-linked polymer and HDI-trimethylol hexyl lactone cross-linked polymer. From the results of Comparative Example 8, it can be seen that if the nano-silicon dioxide dispersion and the silicon carbide nano-whisker dispersion are not prepared, the components are mixed and dispersed unevenly when the lost foam material is mixed, resulting in reduced lost foam performance, and then greatly reduced casting performance. From the results of Comparative Examples 9 and 10, it can be seen that if no or a small amount of silicon carbide titanium MAX phase ceramic material (Ti3SiC2) is added to the lost foam coating, the quality of the casting is reduced.

Claims

1. A method for preparing lost foam casting of composite foam plastic microbeads, characterized in that: The method comprises the following steps: S1, raw material preparation: Prepare raw materials by mass: 45-55 parts of polystyrene foam microbeads, 18-22 parts of polymethyl methacrylate foam microbeads, 12-16 parts of styrene-methyl methacrylate resin powder, 12-16 parts of polyetherimide foam microbeads, 6-10 parts of nano-silicon dioxide, 4-8 parts of silicon carbide nanowhiskers, 3-6 parts of HDI-PPG-polycaprolactone cross-linked polymer, 3-6 parts of HDI-trimethylol hexyl lactone cross-linked polymer, 1.5-3.5 parts of calcium stearate, 0.3-1 part of azodicarbonamide, 0.5-1 part of dimethyl silicone oil, 0.3-0.8 parts of sodium hexametaphosphate and 0.1-0.3 parts of hindered phenol antioxidant 1010; S2, raw material pretreatment: S2.1: drying polystyrene foam plastic microbeads, polymethyl methacrylate foam plastic microbeads, styrene-methyl methacrylate resin powder, and polyetherimide foam microbeads respectively; drying nano-silicon dioxide and silicon carbide nano-whiskers respectively; S2.2: dispersing nano-silicon dioxide in ethanol with a mass of 5 to 10 times the mass of the nano-silicon dioxide to obtain a nano-silicon dioxide dispersion; dispersing silicon carbide nanowhiskers in acetone with a mass of 6 to 10 times the mass of the silicon carbide nanowhiskers to obtain a silicon carbide nanowhiskers dispersion; dissolving sodium hexametaphosphate in deionized water with a mass of 5 to 8 times the mass of the sodium hexametaphosphate to obtain a sodium hexametaphosphate solution; S3, premix: S3.1: Add the dried polystyrene foam microbeads, polymethyl methacrylate foam microbeads, styrene-methyl methacrylate resin powder, and polyetherimide foam microbeads into a mixer in sequence, and stir at a low speed of 300 rpm to 500 rpm for 3 min to 5 min to mix the microbead system evenly; S3.2: Add the nano-silicon dioxide dispersion and the silicon carbide nano-whisker dispersion into the mixer in sequence, and continue stirring at a medium speed of 800 rpm to 1000 rpm for 5 min to 8 min to uniformly disperse the nano-materials in the micro-bead system; S3.3: Add the sodium hexametaphosphate solution into the mixer and stir at a high speed of 1200 rpm to 1500 rpm for 3 min to 5 min; S4, cross-linking and additive mixing: S4.1: Add HDI-PPG-polycaprolactone cross-linked polymer and HDI-trimethylol hexyl lactone cross-linked polymer into the mixer in sequence, stir at a medium speed of 800 rpm to 1000 rpm for 20 min to 30 min at a temperature of 60°C to 80°C, so that the cross-linked polymer is evenly wrapped on the surface of the microbeads and a cross-linking reaction occurs, and evaporate and remove excess ethanol, acetone and deionized water, and cool to room temperature; S4.2: Add calcium stearate, azodicarbonamide and dimethyl silicone oil to the mixer in sequence, and stir at a low speed of 300 rpm to 500 rpm for 3 min to 5 min; finally add hindered phenol antioxidant 1010, and continue stirring at a low speed of 300 rpm to 500 rpm for 2 min to 5 min to obtain a mixture; S5, Foaming: S5.1: Add the mixed material into the mold, set the mold temperature to 60°C to 80°C, press the mold at a pressure of 5MPa to 10MPa for 3min to 5min, and allow the mixed material to foam in the mold to form a preform of the lost foam; S5.2: The formed lost foam blank is retained in the mold and subjected to heat preservation treatment at 60°C to 70°C for 12h to 24h. After cooling and demoulding, the casting lost foam is obtained.

2. The method for preparing lost foam casting by composite foam plastic microbeads according to claim 1, characterized in that: In S1, the particle size range of the polystyrene foam plastic microbeads, polymethyl methacrylate foam plastic microbeads, and polyetherimide foam microbeads are all 0.1 mm to 1 mm; the particle size range of the styrene-methyl methacrylate resin powder is all below 0.3 mm.

3. The method for preparing lost foam casting by composite foam plastic microbeads according to claim 1, characterized in that: In S1, the particle size range of the nano-silicon dioxide is below 150 nm; the diameter range of the silicon carbide nano-whisker is 0.2 μm to 0.7 μm, and the length range of the silicon carbide nano-whisker is 10 μm to 35 μm.

4. The method for preparing lost foam casting of composite foam plastic microbeads according to claim 1, characterized in that: In S2.1, the drying temperatures of the polystyrene foam plastic microbeads, polymethyl methacrylate foam plastic microbeads, styrene-methyl methacrylate resin powder, and polyetherimide foam microbeads are all 40° C. to 50° C., and the drying times are all 2 h to 3 h.

5. The method for preparing lost foam casting of composite foam plastic microbeads according to claim 1, characterized in that: In S2.1, the drying temperature of the nano-silicon dioxide and the silicon carbide nano-whiskers is 100° C. to 120° C., and the drying time is 1 h to 2 h.

6. The method for preparing lost foam casting by composite foam plastic microbeads according to claim 1, characterized in that: In S2.2, the nano-silicon dioxide is dispersed in ethanol and subjected to ultrasonic treatment at a frequency of 30 kHz to 50 kHz for 20 min to 30 min.

7. The method for preparing lost foam casting of composite foam plastic microbeads according to claim 1, characterized in that: In S2.2, the silicon carbide nanowhiskers are dispersed in acetone and ultrasonically treated at a frequency of 40 kHz to 60 kHz for 30 min to 40 min.

8. The method for preparing lost foam casting of composite foam plastic microbeads according to claim 1, characterized in that: In S5.1, the foaming volume ratio of the foam molding is 3 to 5 times.

9. The method for preparing lost foam casting of composite foam plastic microbeads according to claim 1, characterized in that: The method further comprises S6, coating application: The lost foam casting is coated with lost foam coating by a dipping method, and after drying, a coated lost foam casting is obtained.

10. The method for preparing lost foam casting of composite foam plastic microbeads according to claim 9, characterized in that: In S6, the dipping method includes the following steps: each dipping time is 3s to 5s, and the dipping is performed 2 to 4 times; the coating thickness of the lost foam coating is 0.5mm to 2mm; the lost foam coating includes the following raw materials in parts by mass: 42 to 48 parts of zircon powder, 12 to 18 parts of silicon carbide titanium MAX phase ceramic material, 22 to 28 parts of phenolic resin, 3.5 to 4.5 parts of sodium carboxymethyl cellulose, 18 to 22 parts of ethanol, 0.6 to 0.8 parts of n-octanol, 0.5 to 1 part of micro powder wax, 1 to 2 parts of sodium hexametaphosphate and 2 to 3 parts of dibutyl phthalate; the particle size range of the zircon powder is 5μm to 300μm; the particle size range of the silicon carbide titanium MAX phase ceramic material is below 3μm; the particle size range of the micro powder wax is below 30μm.

Citation Information

Patent Citations

  • Vacuum negative-pressure los mould casting technique

    CN101332501A

  • High-foaming expendable casting material and preparation method thereof

    CN103819859A